CEPHALOMETRIC EFFECTS OF THE TWIN BLOCK DEVICE IN ADOLESCENTS WITH MALOCCLUSION - Черненко, Сергей Владимирович; Корчемная, Ольга Сергеевна; Киселева, Елена Александровна (Medicine in Kuzbass, 2024)
Class II malocclusions are most commonly seen in orthodontic practice and in the recent times Twin Block appliance has been the most popular and widely used among removable functional appliances for the correction of Class II malocclusion in growing patients. The aim of this retrospective study was to evaluate the dentoskeletal effects produced by the Twin Block appliance for the correction of Class II division 1 malocclusion with retrognathic mandible.